已知(1+x)^6*(1-2x)^5=a0+a1x+a2x^2+…+a11x^11求1.a1+a2+…+a112.a0+a2+a4+…+a10
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 18:08:07
已知(1+x)^6*(1-2x)^5=a0+a1x+a2x^2+…+a11x^11求1.a1+a2+…+a112.a0+a2+a4+…+a10已知(1+x)^6*(1-2x)^5=a0+a1x+a2x
已知(1+x)^6*(1-2x)^5=a0+a1x+a2x^2+…+a11x^11求1.a1+a2+…+a112.a0+a2+a4+…+a10
已知(1+x)^6*(1-2x)^5=a0+a1x+a2x^2+…+a11x^11
求1.a1+a2+…+a11
2.a0+a2+a4+…+a10
已知(1+x)^6*(1-2x)^5=a0+a1x+a2x^2+…+a11x^11求1.a1+a2+…+a112.a0+a2+a4+…+a10
令x=0
则(1+0)^6*(1-2*0)^5=a0+a1*0+a2*0+……+a11*0
1=a0
令x=1
则(1+1)^6*(1-2*1)^5=a0+a1*1+a2*1+……+a11*1
所以-64=x0+a1+a2+…+a11
所以a1+a2+…+a11=-64-1=-65
令x=-1
则(1-1)^6*(1+2*1)^5=a0+a1*(-1)+a2*(-1)^2+……+a11*(-1)^11
所以0=a0-a1+a2-……-a11
-64=x0+a1+a2+…+a11
相加
2(a0+a2+a4+…+a10)=-64
a0+a2+a4+…+a10=-32
(1) x-3/x-2 - x-5/x-4=x-7/x-6 - x-9/x-8(2) 已知x+3/(x-2)^2=A/x-2 + B/(x-2)^2 ,求A和B的值.
已知集合A={x|6x^2-1>=0},B={x|-x^2+4x+5
已知a=x^3-5x^2,b=x^2-11x+6,求1a-2b
已知不等式x/2-1>x与ax-6>5x同解,a=( )
已知集合A={x|x^2-5x-6
已知集合A={x|x^2-6x+5
已知集合A={x|(x-5)/(x+1)
已知集合A={x|x+1/2-x
已知函数f(x)=(2-a)x+1,x
已知集合A={x|(x-1)(2-x)
已知集合A ={x|(x+1)(x-2)
已知A=x^2-2x+1,B=2x^2-6x+3
已知集合A={x|(x-2)*(x+1)>0},B={x|4x+a
已知集合A={x|x≤-1或x≥5}B={x|-2
已知:(4x+1)/(x-2)(x-5)=A/(x-5)+B/(x-2),则A= ,B=已知:(4x+1)/(x-2)(x-5)=A/(x-5)+B/(x-2),则A= ,B=
已知关于x的方程x=a+x/2+x/6+x/12+x/20+...+x/9900的解为x=-1,求a的值
已知(5x+1)/[(x-1)(x-2)]=A/(x-1)+B/(x-2),求A-B的值
已知:(5x+1)/(x-1)(x-2)=A/(x-1)+11/(x-2),求A的值